METHODS FOR ASSESSING THE EFFECTIVENESS OF THE PERSONNEL MANAGEMENT SYSTEM (Academia Science Repository, 2023)
The main problems of assessing the personnel management system of an enterprise are considered, methods for assessing the personnel management system of an enterprise are studied. A systematic description of personnel management as a system of an integrated subsystem of an organization is presented. Some general properties inherent in personnel management systems and signs of classification of personnel management systems are formulated, taking into account hypotheses.